Post-annealing effects on (00l) texture, Cl/Se ratio, and electrical and glass-like thermal transport in Bi₄O₄SeCl₂ - Somdock, Nuttakrit; Theekhasuk, Nattharika; Voraud, Athorn; Limsuwan, Pichet; Naemchanthara, Kittisakchai; Sakulkalavek, Aparporn; Sakdanuphab, Rachsak; Kaewjumras, Yongyut (My University, 2026)
Bi₄O₄SeCl₂ is a heteroanionic layered material with intrinsically low lattice thermal conductivity and anisotropic charge transport. In this work, the effects of post-annealing temperature on the crystallographic texture, anion chemistry, defect evolution, and transport properties of Bi₄O₄SeCl₂ were systematically investigated. Polycrystalline Bi₄O₄SeCl₂, synthesized by solid-state reaction combined with high-energy ball milling, was post-annealed at 400–700 °C. X-ray diffraction and electron microscopy revealed that post-annealing eliminated the residual BiOCl precursor phase, enhanced the (00 l) preferred orientation, and promoted grain growth up to 600 °C, followed by partial texture degradation at 700 °C due to recrystallization. Energy-dispersive spectroscopy showed progressive Se and Cl volatilization during annealing, leading to an increased Cl/Se ratio. The carrier mobility and electrical conductivity reached maximum values at 600 °C, consistent with improved texture and layered-domain connectivity. Thermal transport remained lattice-dominated and only weakly temperature-dependent. The phonon mean free path, estimated using kinetic theory, was in the sub-nanometer range (∼0.25–0.57 nm), comparable to the interatomic spacing, indicating glass-like phonon transport. Representative HRTEM observations also revealed dislocation-related lattice defects and locally distorted regions, suggesting that vacancy disorder and local strain fields may provide additional phonon scattering. These results demonstrate that post-annealing optimizes electrical transport through phase purification, texture development, and defect-mediated carrier regulation, while the lattice thermal conductivity remains fundamentally limited by intrinsic glass-like phonon transport in Bi₄O₄SeCl₂.
Keywords: (00 l) orientation; Annealing process; Bi4O4SeCl2; Glass-like thermal transport